PERAN PENGUASAAN BAHASA AKADEMIK DALAM MENINGKATKAN PRESTASI BELAJAR AKUNTANSI - Sadiyani, NI Wayan; Fazalani, Runi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the level of academic language mastery and learning achievement of accounting students and to analyze the role of academic language mastery in improving students’ learning achievement. This research employed a quantitative approach with a descriptive correlational design. The population consisted of students of the Accounting Department at Politeknik Negeri Bali, with samples selected using simple random sampling. Data on academic language mastery were collected using a Likert-scale questionnaire, while learning achievement data were obtained from students’ Grade Point Average (GPA) records. Data were analyzed using descriptive statistics and simple linear regression analysis. The results show that the mean score of students’ academic language mastery was 78.45 with a standard deviation of 6.21, which falls into the high category. Students’ learning achievement had a mean GPA of 3.42 with a standard deviation of 0.31, categorized as good. The regression analysis indicates that academic language mastery has a significant role in improving learning achievement, with a significance value of 0.000 (< 0.05) and a contribution of 31.6%. These findings indicate that academic language mastery is an important factor in supporting accounting students’ academic achievement.